Answer:
4v+3 + 5v +6=180
ans is v=19
hope so its the ans
Step-by-step explanation:
mark as brainliest plzzz
The answer to your question is A
Answer: 0
To find this answer, we replace x with 0 in the g(x) function
g(x) = -2x
g(0) = -2*0
g(0) = 0
The general rule for the nth term of the sequence is ![a(n)=-6b+(n-1)(3b)](https://tex.z-dn.net/?f=a%28n%29%3D-6b%2B%28n-1%29%283b%29)
Explanation:
The sequence is -6b, -3b, 0b, 3b, 6b, .....
To find the nth term of the sequence, we need to find the common difference and the first term of the sequence.
First term of the sequence = -6b
Common difference = ![-3b-(-6b)=-3b+6b=3b](https://tex.z-dn.net/?f=-3b-%28-6b%29%3D-3b%2B6b%3D3b)
Using this the nth term of the sequence can be determined.
Since, this is an arithmetic sequence, the general form of AP is given by the formula,
![a(n)=a+(n-1)d](https://tex.z-dn.net/?f=a%28n%29%3Da%2B%28n-1%29d)
where a denotes the first term of the sequence and d denotes the common difference. Thus,
and ![d=3b](https://tex.z-dn.net/?f=d%3D3b)
Substituting the values in the general formula, we get,
![a(n)=-6b+(n-1)(3b)](https://tex.z-dn.net/?f=a%28n%29%3D-6b%2B%28n-1%29%283b%29)
Thus, the general rule for the nth term of the sequence is ![a(n)=-6b+(n-1)(3b)](https://tex.z-dn.net/?f=a%28n%29%3D-6b%2B%28n-1%29%283b%29)